2012
DOI: 10.1111/j.1439-0426.2012.02058.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric variation of snakehead fish,Channa punctatus, populations from three Indian rivers

Abstract: The present study was undertaken with the objective to investigate the intraspecific variation of Channa punctatus on the basis of morphometric characters using the truss network system that was constructed from the fish body. Fish samples were collected from the Narora (n = 62) and Kanpur sites (n = 46) of the Ganga River, the Firozabad site in the Yamuna River (n = 66) and at the Lucknow site of the Gomti River (n = 60). Data were subjected to principal component analysis, discriminant function analysis and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
29
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 18 publications
6
29
1
1
Order By: Relevance
“…In the present paper, 78% of individuals were correctly classified into their respective groups by DFA, indicating high (2010) applied DFA and PCA on three populations of Labeo calbasu from river Jamuna, Halda and hatchery, and reported morphological discrimination among them due to the environmental factors and local migration of the fish. Similar observations were noticed by Khan, Miyan & Khan (2012) in case of Channa punctatus from three Indian rivers and lead the conclusion that environmental conditions play an important role in spatial distribution, movement and isolation of fish stocks. Mir, Mir & Chandra (2014) observed similar inferences in Schizothorax curvifrons from Indus river basin, and attributed to changing physical and ecological conditions of water bodies.…”
Section: Discussionsupporting
confidence: 69%
“…In the present paper, 78% of individuals were correctly classified into their respective groups by DFA, indicating high (2010) applied DFA and PCA on three populations of Labeo calbasu from river Jamuna, Halda and hatchery, and reported morphological discrimination among them due to the environmental factors and local migration of the fish. Similar observations were noticed by Khan, Miyan & Khan (2012) in case of Channa punctatus from three Indian rivers and lead the conclusion that environmental conditions play an important role in spatial distribution, movement and isolation of fish stocks. Mir, Mir & Chandra (2014) observed similar inferences in Schizothorax curvifrons from Indus river basin, and attributed to changing physical and ecological conditions of water bodies.…”
Section: Discussionsupporting
confidence: 69%
“…A study by Mir et al (2013b) demonstrated morphological variation in the caudal area in a cyprinid, Indian major carp, Labeo rohita (Hamilton, 1822), from six drainages of Ganges basin differing in current velocity. Khan et al (2013) have also found variation in the caudal area of a Channidae fish, Channa punctata (Bloch, 1793), from the Ganges basin in India.…”
Section: Discussionmentioning
confidence: 99%
“…The present results are similar to those of Pathak et al [22] who reported morphometric variation in Macrognathus pancalus from two different river basins of India. Khan et al [11] also discriminated the subpopulations of C. punctatus collected from three different rivers (Ganga, Yamuna, and Gomti) of India where the differences were in the head, abdomen, and caudal peduncle regions. The major contributions to DFA and PCA were the measurements belonging to these regions including the high allometric shape contributions from diagonal body measurements.…”
Section: Resultsmentioning
confidence: 99%
“…Working on Indian fishes like Catla catla, Rastrelliger kanagurta, and Megalaspis cordyla, a limited number of workers used the truss morphometry to discriminate the stocks [8][9][10]. A survey of literature showed that no such work on morphometric variations using truss was carried out on C. punctatus so far, except for the work carried out by Khan et al [11]. Therefore, the present study was carried out to find out the morphometric variations employing truss network system using modern geometric morphometric methods to segregate the phenotypic stocks of C. punctatus collected from different isolated geographical sites.…”
Section: Introductionmentioning
confidence: 99%